CO2 Elevation and Photoperiods North of Seed Origin Change Autumn and Spring Phenology as Well as Cold Hardiness in Boreal White Birch - Tedla, Binyam; Dang, Qing-Lai; Inoue, Sahari (Frontiers in Plant Science, 2020)
Climate change is expected to shift tree species distribution further polewards in the future. These shifts will expose trees to new photoperiod regimes and higher atmospheric carbon dioxide concentration ([CO2]). These factors will likely have interactive effects on the ecophysiological traits of plants, particularly in the boreal region where the climate change will be the most prominent. This study investigated how CO2 elevation and photoperiod regimes interactively influence the timing of bud development, leaf senescence, cold hardiness, and bud break in white birch (Betula papyrifera Marsh.). Seedlings were exposed to ambient ([CO2]) (AC= 400 μmol mol−1) or elevated (EC= 1000 μmol mol−1) and photoperiod regimes (at 48 (seed origin), 52, 55, and 58º N latitude) under controlled environment for two growing seasons. We found that EC advanced the initiation of leaf color change in the fall by 23 days, but delayed the completion date. Leaf senescence started earlier at photoperiods of 55 and 58° N latitude than at those of 48 and 52o N latitudes under EC, but no differences occurred under AC. Additionally, the temperature causing 50% electrolyte leakage (a measure of susceptibility to freezing damage) was more negative at two longest photoperiods under EC (-46 ºC at 55º, -60 ºC at 58º N) than other conditions (>-40 ºC). Budburst occurred earlier at the two longest photoperiods under EC, but the trend was opposite under AC. Our study highlights the complex interaction between photoperiod and CO2 conditions to alter autumnal and spring phenology of birch that is required to ensure successful seedling recruitment in new habitats and thus should be considered in predicting the future distribution and productivity of boreal trees.